Onomasticon of the Hittite pantheon. - Gessel, B. H. L. van (Handbook of Oriental Studies. Section 1 The Near and Middle East, 2001)
The Onomasticon of the Hittite Pantheon by Ben van Gessel was published in 1998. In three years time the work has established itself as the ultimate comprehensive reference work concerning the Hittite pantheon. With the publication of Part Three, the main work will be made accessible to a wider circle of all those interested in the ancient Near East. Moreover, it will prove to be an indispensable key to the abundance of information until now only to be found scattered throughout the Onomasticon . The easy-reference glossaries contain all the (word )forms quoted from Hittite texts in the Onomasticon . A special feature of these glossaries is that they not only give the (English) meaning of the (word) forms, but that they also indicate, where appropriate, in relation to which deities they may appear. Also of importance are the lists of personal and geographical names and festivals included. Part Three further includes additions resulting from new discoveries and corrections of earlier references in the Onomasticon .